EFFECT OF WATER CONTENT IN KNEADING METHOD OF SOLID DISPERSION TECHNIQUE FOR SOLUBILITY ENHANCEMENT - P., Shankarguru; D., Ramya Devi; Bn, Vedha Hari (International Journal of Applied Pharmaceutics, 2017)
Objective: The main objective of the research work was to optimize the water requirement/content used in kneading method for solid dispersion/inclusion complex formation between water insoluble drug and polymer. Methods: Nimesulide (model drug) and β-cyclodextrin were taken in a different ratio such as 1:1, 1:3 and 1:5 and, the mixture was triturated well for half hour. Water was incorporated to the mixture in different levels like 75%, 50%, 25% w/v in divided proportions and 0% (no water addition, but the mixture was triturated continuously). After each part of water addition, the mixture was triturated well for 10 min and dried using hot air over for 30 min at 50 °C and sieved using sieve no: 44. The complexes formed were subjected for various analytical characterization studies including solubility, particle size, the angle of repose, tapped density, Carr's index, fourier transform infrared spectrometry (FTIR), thermo gravimetric-differential thermal analysis (TG-TDA), x-ray diffraction (XRD) studies and in vitro dissolution studies. Results: The dissolution studies showed improvement in the release of nimesulide, which depended on the percentage level of water. The solubility of the sample was increased with increasing the concentration of the inclusion complex formed. Kneading method was proved to be a successful technique for formation of stable inclusion complex of nimesulide with β-cyclodextrin. All the formulations exhibited acceptable particle size and solubility in the range of 22.6±2 to 29±5 and 45±5 to 133±3.5 respectively. Conclusion: Nimesulide and β-cyclodextrin complex was successfully prepared and characterized for the drug-polymer stability and interactions. The result confirmed that the liquid content in the solid dispersion prepared by the kneading method played an important role in the dissolution of the poorly soluble drug.